2013
DOI: 10.1186/1471-2229-13-155
|View full text |Cite
|
Sign up to set email alerts
|

The ORCA2 transcription factor plays a key role in regulation of the terpenoid indole alkaloid pathway

Abstract: BackgroundThe terpenoid indole alkaloid (TIA) pathway leads to the production of pharmaceutically important drugs, such as the anticancer compounds vinblastine and vincristine. Unfortunately, these drugs are produced in trace amounts, causing them to be very costly. To increase production of these drugs, an improved understanding of the TIA regulatory pathway is needed. Towards this end, transgenic Catharanthus roseus hairy roots that overexpress the ORCA2 TIA transcriptional activator were generated and chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 47 publications
1
70
1
Order By: Relevance
“…Yeast one-hybrid screening with a Str promoter indicated that ORCA2 activates the Str promoter and its expression is rapidly inducible with JA and fungal elicitation; in contrast, ORCA1 is expressed constitutively and is not involved in JAand fungal elicitor-induced Str gene expression [31]. Recently, the overexpression of ORCA2 in C. roseus hairy roots enhanced the transcript levels of AS, TDC, G10H, STR, D4H, T16H, and PRX1 genes [37]. In addition to the three ORCAs, another transcription factor, the C. roseus box P-binding factor (CrBPF-1) can also bind the Str promoter but at a different position.…”
Section: Regulation Of the Tia Pathwaymentioning
confidence: 99%
See 3 more Smart Citations
“…Yeast one-hybrid screening with a Str promoter indicated that ORCA2 activates the Str promoter and its expression is rapidly inducible with JA and fungal elicitation; in contrast, ORCA1 is expressed constitutively and is not involved in JAand fungal elicitor-induced Str gene expression [31]. Recently, the overexpression of ORCA2 in C. roseus hairy roots enhanced the transcript levels of AS, TDC, G10H, STR, D4H, T16H, and PRX1 genes [37]. In addition to the three ORCAs, another transcription factor, the C. roseus box P-binding factor (CrBPF-1) can also bind the Str promoter but at a different position.…”
Section: Regulation Of the Tia Pathwaymentioning
confidence: 99%
“…C. roseus G10H [50] Ajmalicine:, lochnericine:, tabersonine: Arabidopsis DXS ? feedback-insensitive Arabidopsis ASa [50] Lochnericine:, hörhammericine:, tabersonine: C. roseus T16H [49] Strictosidine;, catharanthine;, lochnericine:, hörhammericine;, tabersonine; C. roseus DAT [51] Hörhammericine: C. roseus ORCA3 [35] Lochnericine;, hörhammericine;, tabersonine; C. roseus ORCA2 [37] Strictosidine;, secologanin;, serpentine:, tabersonine;; C. roseus WRKY1 [43] Serpentine::, catharanthine;, tabersonine; C. roseus WRKY2 [44] Serpentine:, tabersonine::, vindoline:::…”
Section: Metabolic Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, determining an increase in the yield or function of the enzymes in the TIA pathway through overexpression of CrMYC1 cannot confirm that they are the main targets of this transcription factor because CRMYC1 may indirectly enhance the function of some TIA enzymes by targeting another one or more regulatory genes. Similarly, overexpression of ORCA2 transcription factor in Catharanthus roseus hairy root resulted in a significant increase in catharanthine content but the amount of vinblastine and vincristine was below the detectable level (Li et al, 2013). However, there are some limitations for detailed investigation since the catharanthine production pathway is not recognized genetically and enzymatically.…”
Section: Discussionmentioning
confidence: 99%